Reactive oxygen species drive the aberrant immune response to a C. neoformans chitin synthase 3 (chs3Δ) mutant - Watson, Rebekah G.; Hole, Camaron R. (Frontiers in Immunology, 2025)
Cryptococcus neoformans is a globally distributed fungal pathogen that causes severe opportunistic infections, particularly in individuals with impaired cell-mediated immunity, such as AIDS patients and organ transplant recipients. Chitosan, a deacetylated derivative of chitin, plays a key role in modulating immune responses during Cryptococcus neoformans infection. We previously showed that mice inoculated with a heat-killed (HK) chitosan-deficient C. neoformans strain lacking chitin synthase 3 (chs3Δ) undergo rapid, neutrophil-dependent mortality within 36 hours, despite the absence of viable organisms. Here, we investigated the immune mechanisms underlying this lethal inflammatory response. We assessed the role of inflammatory cytokines, adaptive immunity, and neutrophil-derived effector functions in this lethal response. IL-6–deficient and Rag1–deficient mice exhibited only modest survival benefits, suggesting that IL-6 signaling and adaptive immune cells play limited roles. In contrast, mice lacking NADPH oxidase 2 (NOX2), the catalytic subunit of the phagocyte oxidase complex required for reactive oxygen species (ROS) production, were completely protected. Despite equivalent pulmonary neutrophil recruitment in wild-type and NOX2-deficient mice, only the former displayed elevated proinflammatory cytokine and chemokine levels and succumbed to disease. These findings indicate that neutrophils are not intrinsically pathogenic but mediate lethal immunopathology through ROS-dependent inflammatory amplification.